2022
DOI: 10.3390/metabo12100984
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Regulation of Exogenous Hormones on the Absorption of Elements and the Accumulation of Secondary Metabolites in the Medicinal Plant Artemisia argyi Leaves

Abstract: As an important medicinal plant, we still do not know the effect of exogenous hormones on absorption of elements and accumulation of secondary metabolites in Artemisia argyi leaves. In this work, we analyzed the difference in 21 elements absorbed by A. argyi leaves under three exogenous hormone (MeJA, SA and ABA) treatments, and also clarified the correlation between 21 elements and eight bioactive components. Different hormone treatments changed the absorption and enrichment of elements, and the composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Collecting, identifying, and analyzing baseline data was similar to that reported in a recent study by Yang et al. ( 15 ). The p-value was adjusted by Benjamini–Hochberg’s approach.…”
Section: Methodsmentioning
confidence: 69%
“…Collecting, identifying, and analyzing baseline data was similar to that reported in a recent study by Yang et al. ( 15 ). The p-value was adjusted by Benjamini–Hochberg’s approach.…”
Section: Methodsmentioning
confidence: 69%
“…In apple, it has been reported that auxin has the ability to regulate anthocyanin biosynthesis via the Aux/IAA-ARF signaling pathway [ 57 ]. In A. argyi , previous studies have shown that exogenous hormone (MeJA, SA and ABA) treatments changed the eight secondary metabolites, including phenylpropanoids, flavonoids, terpenoids, alkaloids, and others [ 58 ]. In our study, the expression levels of 12 AaIAA genes changed to varying degrees in response to IAA, SA, MeJA, and ABA, and various hormones had an impact on the accumulation of secondary metabolites in A. argyi .…”
Section: Discussionmentioning
confidence: 99%
“…Most of proteomic studies in medicinal plants focus on investigating protein abundance changes under different environmental conditions (Figure 3, blue part). For instance, illumination , temperature, drought Zhang et al, 2022a), flood, saline (Fortini et al, 2022), exogenous hormone (Yang et al, 2022), air composition and planting style are the main factors affecting the content of enzymes or regulators involved in metabolites biosynthesis in the medicinal plants. Unlike abiotic conditions, studies that investigate the effects of biotic stresses on the proteins influencing accumulation of active compounds in traditional medicinal plants are relatively less.…”
Section: Proteomic Dissection Of Medicinal Plants In Different Manner...mentioning
confidence: 99%